Impact-Echo Method on Short Cylinders: A Numerical and Experimental Investigation - Pelekis, Panagiotis; Siorikis, Vassilis G.; Antonopoulos, Constantinos P.; Osmani, Geraldo L.; Hatzigeorgiou, George D. (Salehan Institute of Higher Education, 2025)
Despite the widespread use of Ultrasonic Pulse Velocity (UPV) to estimate the dynamic properties of materials, the accuracy of its results for concrete and rock cylinders, even though it does not depend on cylinder slenderness, is directly affected by the a priori assumption of a specific value of the Poisson's ratio ( ), which can lead to errors of up to 50% in the calculation of the dynamic modulus of elasticity (Ed). In contrast, the Impact Echo (IE) method allows the calculation of Ed without the need-to-know Poisson’s ratio, with an error of approximately 2%, but its results are affected not only by the slenderness ratio (L/D) but also by the inertia effect and the mass of the sensor. In this study, both UPV and IE—longitudinal and torsional—tests were carried out on cylindrical steel and aluminium specimens for six different slenderness values and L/D values ranging from 1-5. The experimental results fully confirm the authors’ proposed shape correction factor (SCF). A numerical analysis of short cylinders is conducted to examine how the mass of the accelerometer used on the IE affects the results. Specifically, aluminium and steel specimens with six different slenderness values were simulated via the finite element method (FEM) via experimental evaluation. Inertia and mass interactions significantly affect the results. Two new correction factors were proposed for steel and aluminium cylinders to address this issue, and three different combinations of NDTs were tested to find that the dynamic properties are very sensitive to these parameters. Poisson’s ratio has been accurately calculated for steel and aluminium cylinders and can be calculated for concrete and rock cores by applying the proposed correction factors.